Infantile and early childhood onset of mitochondrial myopathy due to mutations in the TK2 gene with a phenotype of spinal muscular atrophy 5q: the first cases in Russia - Kurbatov, S. A.; Tsygankova, P. G.; Mollaeva, K. Yu; Bychkov, I. O.; Itkis, Yu. S.; Zabnenkova, V. V.; Umakhanova, Z. R.; Geybatova, L. G.; Zakharova, E. Yu (Nervno-myshechnye bolezni, 2019)
Introduction. Mitochondrial myopathy with thymidine kinase 2 deficiency and spinal muscular atrophy 5q (SMA-5q) are two potentially curable hereditary diseases with different levels of damage to the neuromuscular system and etiology. Early childhood forms have a similar phenotype and are difficult for differential diagnosis.The aim of the study — the description of the clinical and paraclinical characteristics of the mitochondrial myopathy with TK2 deficiency and informing health care specialists about the possibility of optimizing differential diagnosis.Materials and methods. This study involved patients with a previously excluded by molecular genetic method a spinal muscular atrophy 5q diagnosis. Clinical and paraclinical descriptions are presented for 5 patients from 3 families. In addition, 96 patient samples were obtained from the archive of the Research Center for Medical Genetics. The diagnosis based on the clinical and paraclinical features of the disease and the detection of mutations in TK2 gene by sequencing of the NGS panel or TK2 gene directly.Results. Eight patients with mitochondrial myopathy with TK2 from 5 unrelated families have been diagnosed. Three of them have been found retrospectively by analyze of 96 spinal muscular atrophy 5q negative samples.Conclusions. Clinical and molecular genetic characteristics of mitochondrial myopathy with TK2 are presented. The feasibility of differential diagnosis of this rare myopathy with other neuromuscular diseases, including such frequent as spinal muscular atrophy 5q, is shown. The study revealed four previously undescribed mutations in the TK2 gene (c.169G>A (p.Gly57Ser), c.310C>T (p.Arg104Cys), c.338T>A (p.Val113Glu), c.655T>C(p.Trp219Arg)).